Safety and Effectiveness of Liposuction Modalities in Managing Lipedema: Systematic Review and Meta-analysis - Mortada, Hatan; Alaqil, Sultan; Jabbar, Imtinan Al, Medical Student; Alhubail, Fatimah, Medical Student; Pereira, Nicolas; Hong, Joon Pio; Alshomer, Feras (Archives of Plastic Surgery, 2024)
Background Lipedema is a chronic, incurable disorder characterized by painful fat accumulation in the extremities. While the application of liposuction in lipedema management has become increasingly popular, the safety and effectiveness of this approach remain contentious. Our systematic review and meta-analysis aimed to assess various liposuction modalities in lipedema management to verify their safety and efficacy.Methods In-line with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, we performed a comprehensive literature review from inception until March 2023 using the following electronic databases: CENTRAL, MEDLINE, Google Scholar, and EMBASE.Results From the 562 initially identified articles, 20 met our inclusion/exclusion criteria for evaluation. Our review encompassed 14 prospective cohort studies, 3 retrospective studies, 2 case series, and 1 cross-sectional study. A meta-analysis of nine articles revealed a notable improvement in the quality of life, pain, pressure sensitivity, bruising, cosmetic impairment, heaviness, walking difficulty, and itching among lipedema patients who underwent liposuction. Although complications such as inflammation, thrombosis, seroma, hematoma, and lymphedema-related skin changes were reported, severe complications were rare. Crucially, no instances of shock, recurrence, or mortality were reported.Conclusion Liposuction is a safe and beneficial therapeutic intervention for managing lipedema symptoms and enhancing quality of life. However, the impact of liposuction on secondary lymphedema remains unreported in the literature. Further high-quality, large-scale trials are necessary to assess the safety and effectiveness of different liposuction modalities. These studies will contribute valuable insights to optimize liposuction as a therapeutic option for individuals with lipedema.Level of Evidence I, risk/prognostic study.
Keywords: lipedema; liposuction; lipoedema; liposculpture; lipoplasty; quality of life; suction-assisted lipectomy